Association Between Lipids and Arterial Stiffness for Primary Cardiovascular Prevention in a General Middle-Aged European Population - Vallée, Alexandre (Frontiers in Cardiovascular Medicine, 2022)
Background Dyslipidemia contributes to the progression of arterial stiffness (AS). The purpose of this study was to investigate the association of the different lipid parameters with arterial stiffness index (ASI) in a middle-aged population free of cardiovascular (CV) disease. Methods Among 71,326 volunteers from the UK Biobank population, total cholesterol (TC), triglycerides (TG), low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), lipoprotein (a) [Lp(a)], apolipoproteins A and B (Apo A and Apo B), and ASI were measured. Values for non-HDL, TC/HDL, TG/HDL, and LDL/HDL were calculated. AS was defined as an ASI > 10 m/s. Associations between lipid parameters and ASI were performed using multiple linear logistic regressions. The results reported from univariate models were the squared partial correlation coefficient, r2, and from multivariate models, the adjusted coefficient of determination, R2, to describe the contribution of ASI variability for each lipid parameter. Results We found that TG/HDL was mainly associated with ASI [β = 0.53 (0.01), r2 = 3.66%, p < 0.001 and adjusted β = 0.21 (0.01), R2 = 13.58%, p < 0.001] and AS [odds ratio (OR) = 1.86 (1.80–1.92), r2 = 1.65%, p < 0.001 and adjusted OR = 1.15 (1.13–1.17), R2 = 8.54%, p < 0.001] rather than the others. TG/HDL remained the only lipid parameter that showed added value in linear multivariate models. TG/HDL remained less associated with AS than age (r2 = 5.55%, p < 0.001), mean blood pressure (BP; r2 = 5.31%, p < 0.001), and gender (r2 = 4.44%, p < 0.001), but more highly associated than body mass index (BMI; r2 = 1.95%, p < 0.001), heart rate (HR; r2 = 0.81%, p < 0.001), fasting glucose (r2 = 0.18%, p < 0.001), tobacco (r2 = 0.05%, p < 0.001), and glomerular filtration rate (GFR; r2 = 0.01%, p < 0.001). Conclusions In primary CV prevention, lipids, especially through the TG/HDL ratio, could be more instructive in preventing the increase in AS than other modifiable factors.